Understanding the Adverse Effects of Social Media on Children with Intellectual Disabilities: Parental Insights and Preventive Strategies - Alanazi, Adel; Alqazlan, Sohil (Journal of Cultural Analysis and Social Change, 2025)
Background: This research emphasizes the background issue of social media-based adverse effects on children with intellectual disabilities in Saudi Arabia, along with parents’ perceptions and possible solutions for mitigating such issues. Results: The results derived from the survey method used with Saudi parents indicated that social media had negative emotional, physical, and psychological impacts on children suffering from intellectual disabilities. Parents’ perceptions are also negative of these children’s excessive usage of social media Conclusions: It is concluded that parents must guide these children to limited and positive usage of social media for exchanging information and educational achievements. Parents are also required to keep their children monitored and use the co-surfing of social media accounts to prevent children from cybercrimes, fake relationships, and data privacy issues.